Indicadores estatísticos de desempenho no basquetebol: análise longitudinal e fatores discriminantes de vitória e derrota - Canuto, Sarah Cristina Montes (2022)
Hypertension is a leading risk factors associated with cardiovascular morbidity and mortality, killing millions of people every year. And in hypertension oxidative stress is increased and may be the cause or a consequence of elevated blood pressure. In recent years the exercise has been shown to be an alternative for the prevention and treatment of hypertension to lower blood pressure, as has been demonstrated the ability to strength training improve antioxidant defense in normotensive. Thus, the objectives of this work were: (1) to evaluate the effects of a low-intensity resistance exercise session on oxidative stress indicators in cardiac muscle of hypertensive rats; (2) evaluate the effects of strength training on renal and cardiac hypertrophy-induced renovascular hypertension; (3) evaluate the effects of strength training on renal oxidative stress in rats with renovascular hypertension. We verified that the power exercise can reduce oxidative damage by increasing the activity of antioxidant enzymes in the heart. These effects are similar in the kidney when it is performed strength training chronically with moderate intensity in renovascular hypertension. It was possible to verify that strength training has beneficial effects on hypertension and renovascular is able to reduce mean arterial pressure and heart rate, and reverse hypertrophy of the contralateral kidney and heart.